2023
DOI: 10.1186/s12961-023-00967-x
|View full text |Cite
|
Sign up to set email alerts
|

How transdisciplinary research teams learn to do knowledge translation (KT), and how KT in turn impacts transdisciplinary research: a realist evaluation and longitudinal case study

Abstract: Background Transdisciplinary research and knowledge translation are increasingly regarded as key concepts underpinning applied research across the health and social sciences, due to their presumed potential in addressing complex, “wicked” problems and improving the use of research in practice and policy, respectively. Despite sharing an impact mandate, the relationship between transdisciplinary research collaboration and knowledge translation remains unclear. In response, we examined the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The iterative process of transdisciplinary research employs systems mapping as the underlying mechanism for the identification and evaluation of interventions, whereby transdisciplinary workshops act as the main vehicle for knowledge integration and knowledge translation [72]. Figure 2 presents a schematic overview of key elements of transdisciplinary working.…”
Section: Methodsmentioning
confidence: 99%
“…The iterative process of transdisciplinary research employs systems mapping as the underlying mechanism for the identification and evaluation of interventions, whereby transdisciplinary workshops act as the main vehicle for knowledge integration and knowledge translation [72]. Figure 2 presents a schematic overview of key elements of transdisciplinary working.…”
Section: Methodsmentioning
confidence: 99%
“…Of the five articles in this category, four focus on intragroup dynamics (Curry et al, 2012; Hemmings et al, 2013; Lunde et al, 2013) or composition (Archibald, 2016), and one addresses between-group dynamics (Schieber et al, 2017). The classification of teams within this theme ranges from multidisciplinary (i.e., independent research of various disciplines on a shared issue; Rosenfield, 1992; Archibald et al, 2023; e.g., Lunde et al, 2013) through to interdisciplinary (i.e., sharing of distinct disciplinary perspectives toward a shared problem; e.g., Rosenfield, 1992; Archibald et al, 2023; e.g., Curry et al, 2012; Archibald, 2016). Notably, transdisciplinary mixed methods research articles were not identified.…”
Section: Within and Between Collaborative Team Dynamicsmentioning
confidence: 99%
“…Equally relevant is the boundary spanning that takes place within and between investigative teams, communities, stakeholder groups, and bodies of knowledge. Bridging across boundaries attends to the spirit of diversity characteristic of MMR (Greene, 2007), enables collective responses to complex social problems (Lucero et al, 2018; Poth, 2018), provides opportunities to approach persistent challenges from new angles (Johnson et al, 2007), and reflects broader academic and social movements emphasizing the merits of partnership in improving research capacity, quality, and relevance to end-users (Archibald et al, 2023). Collaboration is a boundary spanning practice that is integral to these objectives.…”
mentioning
confidence: 99%
“…Establishing trust and pathways or channels between stakeholders in complex systems are critical to the flow of evidence and to authentic collaborative communication ( 6 ). Similarly, transdisciplinary environments involved in knowledge translation require strong leadership ( 24 ) but workplace democratization is also a necessary condition. Just as the knowledge translation discourse is increasingly looking towards the organization rather than solely emphasizing individuals' responsibility for research use ( 25 ), so too must discussions of democratization consider workplace structure.…”
Section: Co- Implementation: the What The Where And The Whymentioning
confidence: 99%